Heat Shock Protein 90 Homeostasis Controls Stage Differentiation in Leishmania donovani - Wiesgigl, Martina (The American Society for Cell Biology, 2001)
The differentiation of Leishmania parasites from the insect stage, the promastigote, toward the pathogenic mammalian stage, the amastigote, is triggered primarily by the rise in ambient temperature encountered during the insect-to-mammal transmission. We show here that inactivation of heat shock protein (Hsp) 90, with the use of the drugs geldanamycin or radicicol, mimics transmission and induces the differentiation from the promastigote to the amastigote stage. Geldanamycin also induces a growth arrest of cultured promastigotes that can be forestalled by overexpression of the cytoplasmic Hsp90. Moreover, we demonstrate that Hsp90 serves as a feedback inhibitor of the cellular heat shock response in Leishmania. Our results are consistent with Hsp90 homeostasis serving as cellular thermometer for these primitive eukaryotes, controlling both the heat shock response and morphological differentiation.